Transfer Pricing Regulation and Taxation of Royalty Payments - Steffen Juranek; Dirk Schindler; Guttorm Schjelderup (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We analyze the implications of OECD methods to regulate transfer pricing and the role of a royalty tax for abusive transfer pricing. We show: (i) Under traditional methods, mispricing of royalty payments does not affect investment, but the Transactional Profit Split Method triggers higher investment to facilitate profit shifting. (ii) Royalty taxation reduces both profit shifting and investment. (iii) A royalty tax rate below the corporate tax rate leads to overinvestment in an ACE tax system.
Keywords: H25; H32; F23; 330